Long Non-coding RNA T-uc.189 Modulates Neural Progenitor Cell Fate by Regulating Srsf3 During Mouse Cerebral Cortex Development - Zhang, Meng; Zhou, Junjie; Jiao, Li; Xu, Longjiang; Hou, Lin; Yin, Bin; Qiang, Boqin; Lu, Shuaiyao; Shu, Pengcheng; Peng, Xiaozhong (Frontiers in Neuroscience, 2021)
Neurogenesis is a complex process that depends on the delicate regulation of spatial and temporal gene expression. In our previous study, we found that transcribed ultra-conserved regions (T-UCRs), a class of long non-coding RNAs that contain UCRs, are expressed in the developing nervous systems of mice, rhesus monkeys, and humans. In this study, we first detected the full-length sequence of T-uc.189, revealing that it was mainly concentrated in the ventricular zone (VZ) and that its expression decreased as the brain matured. Moreover, we demonstrated that knockdown of T-uc.189 inhibited neurogenesis. In addition, we found that T-uc.189 positively regulated the expression of serine-arginine-rich splicing factor 3 (Srsf3). Taken together, our results are the first to demonstrate that T-uc.189 regulates the expression of Srsf3 to maintain normal neurogenesis during cortical development.